(untitled) (BEOIBERISTIKA - Časopis za iberijske, latinoameričke i komparativne studije (ISSN: 2560-4163 Online), 2025)
In the story “Los hombres fieras” by Roberto Arlt (Argentina, 1900–1942), the cultural clash between Liberian indigenous people and African American descendants is highlighted, addressing themes such as barbarism, the questioning of Western culture, and integration into foreign worlds. The aim is to explore how the narrative reconsiders moral values, their violation in specific circumstances, and the inherent impulses of human nature, treated in a turbulent and complex manner. From an existentialist and structuralist perspective, the characters’ concerns are analyzed as they face ethical and cultural dilemmas that compel them to redefine their identity. The African jungle, more than a physical space, becomes a symbolic setting where tensions between civilization and barbarism take center stage. The story raises questions about the human condition, imperialism, and migratory processes, transcending temporal and geographical boundaries. In this context, Arlt examines the relationships between power, justice, and belonging, exposing the contradictions of human nature. At the same time, the author encourages reflection on the values underpinning societies and the tensions between the individual and the collective, offering a critical perspective that transcends his time.